Exploring Access to Justice: Perspectives of People with Disabilities within the Framework of Brasilia Rules - Lleellish Juscamayta, Yeniva Isabel (2024)
In this work, we will examine the impact of current policies and practices on access to justice for people with disabilities, focusing especially on the needs of individuals with hearing disabilities. We will explore how the barrier of incomprehension of legal language affects this population and the emergence of accessible language initiatives globally. Specifically, we will discuss the implementation of the Brasilia Rules, highlighting the importance of inclusive language and emphasizing the urgency of adopting concrete measures in Peru. We conclude that the consolidation of inclusive practices not only protects the rights of citizens, including those with hearing disabilities, but also underscores the need for the Peruvian Judiciary to truly achieve equitable justice in the country.